Grammatical deviation in President Jokowi’s speech to the APEC CEO summit - R. Agus Budiharto (Studies in English Language and Education, 2018)
Grammar constitutes not only part of one’s knowledge but also a central component of verbal communication for people who are using language. When speakers use language without using grammar (i.e. the rules regarding how words alter their form and combine with other words to create sentences), it can cause a muddle and also possibly, problems in communication such as grammatical deviation. This present study examines a speech at the APEC CEO Summit in 2014 by President Joko Widodo, from the perspective of grammatical deviation with two foci, via: to find out the types of grammatical deviation spoken by the speaker by employing Leech’s views (1969)and to identify the speaker’s social status by employing the theory of Trudgill (2004). The result from this study shows that some of President Joko Widodo’s speech deviated from the rules, although based on Fromkin et al. (2011)when a person knows a language; he knows the sounds, words and the rules of their combination.